Regional Integration and Natural Resources: who benefits? Evidence from MENA - Céline Carrère; Julien Gourdon; Marcelo Olarreaga (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
This paper is built on Venables (2011) theoretical predictions which show that gains from regional integration are unevenly distributed between resource rich and poor countries. We explore the effects of different integration schemes in Middle East and North Africa. Results suggest that within Pan Arab Free Trade Agreement (PAFTA), there is significant trade creation for resource poor countries associated with regional integration, and no evidence of trade diversion. In resource rich countries, however, there is evidence of pure trade diversion in both resource-rich/labor-abundant countries and resource-rich/labor-importing countries. This underscores the idea that regional integration can help to spread benefits of unevenly distributed resource wealth among the region's economies.
Keywords: F10; F11; 330